A Baghdad chronicle - Levy, Reuben (Cambridge University Press, 2011)
The aim of this 1929 study was to present an account of Baghdad under the Abbasid Caliphate which included not only the record of conflict and political history of the city, but as much as possible of its social history, with descriptions of the manners and customs of its people.